(untitled) (Journal of actual problems of jurisprudence, 2016)
This article discusses current approaches to the concept of plagiarism. Analyzes the methods of counteracting copyright infringement in Kazakhstan. The main tasks of the science of information law. The analysis of the state policy in the field of scientific research integrity. The problems faced by modern science in the fight against plagiarism.